Analysis of Coherence and Cohesion on Students’ Academic Writing: A Case Study at The 3rd Year students at English Education Program - Lismay Leli (Alsuna: Journal of Arabic and English Language, 2020)
Purpose - This research aims to analyze the understanding of coherence and cohesion made by the 3rd year students of English education program on their academic writing at Islamic Institute of Bukittinggi. Design/methodology/approach - This was descriptive research which explains the phenomena concerns on the data due to field finding. This research applied for the library based work where the data was taken by using document analysis and interview. Findings - The result of the research showed that the numbers of students were still difficult to construct the idea cohesively and coherently. The result of the students’ understanding on coherence and cohesion showed that there were 59% students who were considered in need to improve and also followed by good work and could be better with 27% and 14% respectively. It can be explained that students were lack of ability to write the idea smoothly and grammatically correct. The interview result showed that there were three main reasons for this. Those are lack of motivation, limited lecture duration and prior English knowledge. Originality/value - coherence and cohesion are parts of academic writing that should be mastered by students in order to create a good thesis. Specifically for the students who will graduate from Higher Education. Paper type – Research paper